EXPRESSION OF RUSSIAN MENTALITY IN PROVERBS AND SAYINGS OF THE RUSSIAN PEOPLE WITH THE CONCEPT OF "FAMILY" - Bektursinova Aysultan Marat qizi (Western European Studies, 2024)
This article is devoted to the analysis of the Russian linguistic picture of the world, which is represented in a small genre of oral folklore - proverbs. Proverbs with the concept of "family" were selected as the research material
Keywords: proverb; linguistic picture of the world; family; concept